Selective Suprascapular and Axillary Nerve Block Provides Adequate Analgesia and Minimal Motor Block. Comparison with Interscalene Block - Pitombo, Patrícia Falcão [UNESP]; Meira Barros, Rogério; Matos, Marcos Almeida; Pinheiro Módolo, Norma Sueli [UNESP] (Elsevier, 2013)
Background and objective: Shoulder arthroscopic surgeries evolve with intense postoperative pain. Several analgesic techniques have been advocated. The aim of this study was to compare suprascapular and axillary nerve blocks in shoulder arthroscopy using the interscalene approach to brachial plexus blockade. Methods: According to the technique used, sixty-eight patients were allocated into two groups: interscalene group (IG, n. =. 34) and selective group (SG, n. =. 34), with neurostimulation approach used for both techniques. After appropriate motor response, IG received 30. mL of 0.33% levobupivacaine in 50% enantiomeric excess with adrenalin 1:200,000. After motor response of suprascapular and axillary nerves, SG received 15. mL of the same substance on each nerve. General anesthesia was then administered. Variables assessed were time to perform the blocks, analgesia, opioid consumption, motor block, cardiovascular stability, patient satisfaction and acceptability. Results: Time for interscalene blockade was significantly shorter than for selective blockade. Analgesia was significantly higher in the immediate postoperative period in IG and in the late postoperative period in SG. Morphine consumption was significantly higher in the first hour in SG. Motor block was significantly lower in SG. There was no difference between groups regarding cardiocirculatory stability and patient satisfaction and acceptability. Failure occurred in IG (1) and SG (2). Conclusions: Both techniques are safe, effective, and with the same degree of satisfaction and acceptability. The selective blockade of both nerves showed satisfactory analgesia, with the advantage of providing motor block restricted to the shoulder. Justificativa e objetivo: Cirurgias artroscópicas do ombro cursam com intensa dor pós-operatória. Diversas técnicas analgésicas têm sido preconizadas. O objetivo deste estudo foi comparar o bloqueio dos nervos supraescapular e axilar nas cirurgias artroscópicas de ombro com a abordagem interescalênica do plexo braquial. Método: Sessenta e oito pacientes foram alocados em dois grupos de 34, de acordo com a técnica utilizada: grupo interescalênico (GI) e grupo seletivo (GS), sendo ambas as abordagens realizadas com neuroestimulador. No GI, após resposta motora adequada foram injetados 30. mL de levopubivacaína em excesso enantiomérico de 50% a 0,33% com adrenalina 1:200.000. No GS, após resposta motora do nervo supraescapular e axilar, foram injetados 15. mL da mesma substância em cada nervo. Em seguida, realizada anestesia geral. Variáveis avaliadas: tempo para realização dos bloqueios, analgesia, consumo de opioide, bloqueio motor, estabilidade cardiocirculatória, satisfação e aceitabilidade pelo paciente. Resultados: Tempo para execução do bloqueio interescalênico foi significativamente menor que para realização do bloqueio seletivo. Analgesia foi significativamente maior no pós-operatório imediato no GI e no pós-operatório tardio no GS. Consumo de morfina foi significativamente maior na primeira hora no GS. Bloqueio motor foi significativamente menor no GS. Estabilidade cardiocirculatória, satisfação e aceitabilidade da técnica pelo paciente não diferiram entre os grupos. Ocorreu uma falha no GI e duas no GS. Conclusões: Ambas as técnicas são seguras, eficazes com mesmo grau de satisfação e aceitabilidade. O bloqueio seletivo de ambos os nervos apresentou analgesia satisfatória, com a vantagem de proporcionar bloqueio motor restrito ao ombro. © 2013 Elsevier Editora Ltda..
Keywords: Anesthesia, Conduction; Anesthetics, Local/levobupivacaine; Brachial Plexus; Orthopedic Procedures; Shoulder Joint